Beyond Sputnik and the Space Race : The Origins of Global Satellite Communications - Slotten, Hugh Richard (Book collections on Project MUSE., 2022)
"A fascinating account of how the United States established the first global satellite communications system to project geopolitical leadership during the Cold War"--